PENERAPAN METODE PEMBELAJARAN AL-MIFTAH JILID 1 UNTUK MENINGKATKAN KEMAMPUAN QAWAID DASAR DI MTS NURUL IMAN TAROWANG - Hamsir, Muh; Zainal, Abdul Qahar; Sudarmono, Muh Aidil; Muhammad; Martini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of the application of the Al-Miftah learning method Volume 1 in improving the mastery of basic qawaid of class VII.A students of MTs Nurul Iman Tarowang, Jeneponto Regency. This study uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart model which is implemented in two cycles, each of which includes the planning stage, action implementation, observation, and reflection. The research subjects were 33 class VII.A students. Data collection techniques include observation, interviews, tests, and documentation. Data were analyzed using quantitative and qualitative descriptive analysis by calculating the average value and percentage of student learning completion in each cycle. The results of the study indicate that the application of the Al-Miftah method Volume 1 is able to significantly improve students' mastery of basic qawaid. In the pre-cycle stage, the average value was 52.87 with a learning completion percentage of 15.15%. After the implementation of the Al-Miftah Volume 1 method in cycle I, the average value increased to 68.03 with a learning completion of 33.33%. Furthermore, in cycle II, the average value increased to 86.06 with a completion percentage reaching 93.93%, thus exceeding the established research success indicators, namely at least 80% of students achieving the Minimum Completion Criteria (KKM). In addition to improving learning outcomes, the Al-Miftah Volume 1 method also increases student activity, attention, and participation during the learning process. Based on these results, it can be concluded that the Al-Miftah Volume 1 method is effectively applied in Arabic learning because it is able to improve the mastery of basic qawaid of class VII.A students of MTs Nurul Iman Tarowang, Jeneponto Regency. Therefore, this method can be used as an alternative in Arabic learning to improve students' understanding of the basic rules of nahwu and shorof.